The Use Of Laboratory Tests To Study Oil Content In Injection Water Which Tend To Form Emulsion Block And Can Cause Plugging In Reservoir Rock - Tjuwati Makmur (Testing Center for Oil and Gas LEMIGAS, 2008)
Oil content plays important role in determining injection water quality before the injection water is injected into reservoir for water flooding need. Determination of oil contents laboratory tests were carried out on five injection water samples from different gathering stations. The results of tests show that two of five injection water samples contain oil contents which fulfill MIGAS guidelines (25 ppm) requirements specification. Whereas, oil contents in the three injection water samples are in a range of 38.00 ppm and 77.00 ppm. The values of oil contents exceed MIGAS guidelines and tend to form emulsion block and cause the occurrence of plugging in reservoir rock.